Smart Energy Meter Prototype For Single-Phase Power Lines In Peru - Narciso-Celestino, Dalton (2021)
World energy demand is increasing as a result of population growth and industrial development. Nowadays, in Peru, electricity consumption has significantly increased. Elec- tric companies in Peru depend on their staff to record the consumption of meters; on the other hand, users do not have the easiness of monitoring their consumption day by day or the access to the information of their consumption. Given the problem described, in this project, the development of a smart meter based on Wi-Fi communication technology is presented. The Wi-Fi transmission allows saving the consumption of a user in a database. The present research project implements an intelligent electric consumption meter that can calculate and display the monetary expenditure of a residence. The implemented prototype has an electronic system that records the electrical energy consumption by means of sensing the current and voltage signals through a developed algorithm that is able to calculate the electrical energy consumption in kilowatt per hour. This in order to provide the user with easy access to information in real-time and to help them in managing their consumption better. The proposed solution intends to contribute to the saving of electrical energy, which represents a saving in monthly billing for the user and overall a reduction in Peruvian household's CO2 emissions.